NEXUS Gains Talk 17: Energy, water, and multisectoral linkages in Africa - Harou, Julien; Tahavori, Mohammad Amin; Hafeez, Mohsin (CGIAR, 2023)
This NEXUS Gains webinar explores the intricate relationships within the WEFE nexus, focusing on the role of energy systems in Africa. It examines this nexus from the perspective of both small-scale and national energy system modelling, offering insights into the challenges and opportunities at both scales. Presentations review the benefits of linking river basins and regional energy systems for joint intervention assessment and multi-sector strategic planning. Case studies emphasize the critical role of understanding energy demands in rural Africa as a key element in the WEFE nexus and addressing the complex challenges to promoting sustainable development in the region.